2012
DOI: 10.5812/aapm.3590
|View full text |Cite
|
Sign up to set email alerts
|

Whiplash Patients with Cervicogenic Headache After Lateral Atlanto- Axial Joint Pulsed Radiofrequency Treatment

Abstract: Whiplash associated disorders are very costly to any healthcare structure, whatever the policy that shapes it. The prevalence of cervicogenic headache in whiplash injuries are as high as 53%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…In order to emphasize the importance of PRF in the treatment of chronic pain, we have published three reports in this issue ( 10 - 12 ). The authors of these articles reported successful applications of PRF for the treatment of pain conditions, including amputation pain, lumbar facet joint pain, and whiplash pain.…”
mentioning
confidence: 99%
“…In order to emphasize the importance of PRF in the treatment of chronic pain, we have published three reports in this issue ( 10 - 12 ). The authors of these articles reported successful applications of PRF for the treatment of pain conditions, including amputation pain, lumbar facet joint pain, and whiplash pain.…”
mentioning
confidence: 99%
“…This application is now long past its initial stage. Good long term results have been published on the atlanto-axial join ( 7 ). This was a novel aspect of PRF.…”
Section: Introductionmentioning
confidence: 99%
“…1 The incidence of WAD is ~600 per 100.000 persons, 2 and the costs associated with this condition are very high, with the symptom of headache noted as the most burdensome according to patients. 3,4 Different signs and symptoms are present in people with WAD, from neuromusculoskeletal impairments and sensitization [5][6][7][8][9] to psychological disturbances. [9][10][11][12][13][14] Some features such as pain catastrophizing, kinesiophobia, anxiety, and neck disability have been associated with the severity of WAD, both in the acute and chronic stages.…”
mentioning
confidence: 99%
“…According to the International Headache Classification Disorders (ICHD-III), whiplash-associated headache (WAH) is recognized as the development of a new headache or worsening of a pre-existing headache beginning within 7 days after a whiplash injury and is one of many potential symptoms that can present under the diagnosis of whiplash-associated disorders (WAD) 1 . The incidence of WAD is ~600 per 100.000 persons, 2 and the costs associated with this condition are very high, with the symptom of headache noted as the most burdensome according to patients 3,4 …”
mentioning
confidence: 99%